Gastrointestinal and liver disease in Adult Life After Childhood Cancer in Scandinavia: A population‐based cohort study. Issue 7 (2nd June 2016) - Asdahl, Peter Haubjerg; Winther, Jeanette Falck; Bonnesen, Trine Gade; De Fine Licht, Sofie; Gudmundsdottir, Thorgerdur; Holmqvist, Anna Sällfors; Malila, Nea; Tryggvadottir, Laufey; Wesenberg, Finn; Dahlerup, Jens Frederik; Olsen, Jørgen Helge; Hasle, Henrik; et al.
Abstract : Survival after childhood cancer diagnosis has remarkably improved, but emerging evidence suggests that cancer‐directed therapy may have adverse gastrointestinal late effects. We aimed to comprehensively assess the frequency of gastrointestinal and liver late effects among childhood cancer survivors and compare this frequency with the general population. Our population‐based cohort study included all 1‐year survivors of childhood and adolescent cancer in Denmark, Finland, Iceland, Norway and Sweden diagnosed from the 1940s and 1950s. Our outcomes of interest were hospitalization rates for gastrointestinal and liver diseases, which were ascertained from national patient registries. We calculated standardized hospitalization rate ratios (RRs) and absolute excess rates comparing hospitalizations of any gastrointestinal or liver disease and for specific disease entities between survivors and the general population. The study included 31, 132 survivors and 207, 041 comparison subjects. The median follow‐up in the hospital registries were 10 years (range: 0–42) with 23% of the survivors being followed at least to the age of 40 years. Overall, survivors had a 60% relative excess of gastrointestinal or liver diseases [RR: 1.6, 95% confidence interval (CI): 1.6–1.7], which corresponds to an absolute excess of 360 (95% CI: 330–390) hospitalizations per 100, 000 person‐years. Survivors of hepatic tumors, neuroblastoma and leukemia had the highest excess of gastrointestinal and liver diseases. In addition, we observed a relative excess of several specific diseases such as esophageal stricture (RR: 13; 95% CI: 9.2–20) and liver cirrhosis (RR: 2.9; 95% CI: 2.0–4.1). Our findings provide useful information about the breadth and magnitude of late complications among childhood cancer survivors and can be used for generating hypotheses about potential exposures related to these gastrointestinal and liver late effects. Abstract : What's new? Cancer treatment is no walk in the park. After treatment for childhood cancer, many adults experience health problems related to their earlier treatment. This study set out to quantify just how often cancer survivors experience gastrointestinal and liver problems, compared with the general population. The authors pursued a comprehensive approach, scanning for more disorders than the previous Childhood Cancer Survivor Study. Using data from more than 30, 000 cancer survivors and 200, 000 comparison subjects in five countries, they calculated that cancer survivors experience 60% more GI and liver problems than the general public, particularly survivors of neuroblastoma, leukemia and hepatic tumors.